2017
DOI: 10.1074/jbc.m116.766329
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic protein phosphatase 1 regulatory subunit 3B (Ppp1r3b) promotes hepatic glycogen synthesis and thereby regulates fasting energy homeostasis

Abstract: Maintenance of whole-body glucose homeostasis is critical to glycemic function. Genetic variants mapping to chromosome 8p23.1 in genome-wide association studies have been linked to glycemic traits in humans. The gene of known function closest to the mapped region, (protein phosphatase 1 regulatory subunit 3B), encodes a protein (G) that regulates glycogen metabolism in the liver. We therefore sought to test the hypothesis that hepatic is associated with glycemic traits. We generated mice with either liver-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 35 publications
6
61
0
Order By: Relevance
“…Overexpression of PPP1R3B in livers of mice and rats is associated with increased hepatic glycogen content . Similarly, we found that adenovirus‐mediated expression of PPP1R3B at supraphysiological levels in livers of mice caused a dramatic increase in liver weight and hepatic glycogen content (Fig.…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…Overexpression of PPP1R3B in livers of mice and rats is associated with increased hepatic glycogen content . Similarly, we found that adenovirus‐mediated expression of PPP1R3B at supraphysiological levels in livers of mice caused a dramatic increase in liver weight and hepatic glycogen content (Fig.…”
Section: Resultssupporting
confidence: 73%
“…To test the hypothesis that hepatic x‐ray attenuation associated with rs4841132‐A is attributed to an increase in hepatic glycogen content caused by increased expression of PPP1R3B , we examined the hepatic glycogen and TG levels in livers of mice that either lack (KO) or overexpress PPP1R3B. As we were performing these studies, Rader and his colleagues developed liver‐specific Ppp1r3b KO mice . These mice had reduced hepatic glycogen attributed to a reduction in incorporation of glucose into glycogen.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1, Table 3). Interestingly, phenylalanine mutation of GL at tyrosine 284 prevented the allosteric inhibitory binding of phospho-glycogen-phosphorylase to GL, resulting in the dephosphorylation and activation of glycogen synthase [103,104]. Thus, knockin mice that express mutant GL Y284F displayed an enhanced hepatic glycogen synthase activity and improved glucose tolerance, supporting the notion that pharmacological inhibition of this particular GL:phospho-glycogen-phosphorylase interaction can be used to combat diabetic hyperglycaemia [93,103,105,106].…”
Section: Pp1-dependent Functions Of Glycogen-targeting Subunits Gm Anmentioning
confidence: 86%